2002
DOI: 10.1289/ehp.02110689
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds as breath biomarkers for active and passive smoking.

Abstract: We used real-time breath measurement technology to investigate the suitability of some volatile organic compounds (VOCs) as breath biomarkers for active and passive smoking and to measure actual exposures and resulting breath concentrations for persons exposed to tobacco smoke. Experiments were conducted with five smoker/nonsmoker pairs. The target VOCs included benzene, 1,3-butadiene, and the cigarette smoke biomarker 2,5-dimethylfuran. This study includes what we believe to be the first measurements of 1,3-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 47 publications
7
111
1
Order By: Relevance
“…The peaks of acetone, benzene and toluene were also detected in nonsmoker's breath samples; however, these concentrations were clearly higher in the smoker's breath. Additionally, many VOCs were only detected in the smokers' breath; especially, 2,5-DMF has been recognized as a tobacco smoke biomarker in the smoker's breath, 19,20 and actually detected only in the smokers' breath in this work. For all of the smokers' breath samples, the level of ammonia was below the LOD of the commercially-available detection tube.…”
Section: Determination Of Tobacco-related Vocs In Smokers' Breathmentioning
confidence: 60%
“…The peaks of acetone, benzene and toluene were also detected in nonsmoker's breath samples; however, these concentrations were clearly higher in the smoker's breath. Additionally, many VOCs were only detected in the smokers' breath; especially, 2,5-DMF has been recognized as a tobacco smoke biomarker in the smoker's breath, 19,20 and actually detected only in the smokers' breath in this work. For all of the smokers' breath samples, the level of ammonia was below the LOD of the commercially-available detection tube.…”
Section: Determination Of Tobacco-related Vocs In Smokers' Breathmentioning
confidence: 60%
“…As can be seen in Table 2, the maximum concentration levels found for these compounds in non-smokers were always higher than the minimum levels found in smokers. Previous studies [9,12,13] found that benzene content in breath decreases rapidly to pre-exposure levels in less than 1 hour after smoking.…”
Section: Environmental Air and Breath Analysismentioning
confidence: 94%
“…The possibility of using breath tests to evaluate exposure to ETS is very promising given that it is a procedure that is safe and easy to perform. Preliminary studies have suggested that some VOCs detected in breath samples may be biomarkers (e.g., 1,3-butadiene, benzene, 2,5-dimethylfuran) [8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…(Jarvis et al 1980;Kharitonov et al 1995;Wester et al 1986aWester et al , b, 1987aGordon et al 1995;Gordon 1990). To date, smoking status is often used as a major factor in the validation of new technologies for breath analyses as it is well known that toxicity markers of all sorts should be differentiated in smokers versus nonsmokers (Santini et al 2016;Kushch et al 2008;Basanta et al 2010;艩panel and Smith 1996).…”
Section: Toxicity Of Smokingmentioning
confidence: 99%